Self-sensing metallic material based on piezoelectric particles - Ferreira, Pedro M. (2023)
The Authors acknowledge Fundação para a Ciência e a Tecnologia (FCTMCTES) for its financial support via the project UIDB/00667/2020 (UNIDEMI). PMF also acknowledges FCT-MCTES for funding the PhD grant UI/BD/151055/2021.